2007
DOI: 10.1002/anie.200702178
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)‐Reidispongiolide A, an Actin‐Targeting Marine Macrolide

Abstract: Reidispongiolide A (1), isolated by D Auria et al. from the sponge Reidispongia coerulea, which was collected off the coast of New Caledonia, [1] and sphinxolide B (2) [2] are representative members of a structurally unique family of cytotoxic marine macrolides.[3] Their interaction with actin in the cell cytoskeleton leads to microfilament destabilization, and they show potent antiproliferative activity (for example, IC 50 = 0.04 and 0.01 mg mL À1 against human colon carcinoma HT29) and the ability to circumv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…>95:5; d.r.=diastereomeric ratio), according to the well documented 1,5‐ anti (C31–C27) and 1,3‐ syn (C27–C29) stereocontrol in the aldol and reduction processes, respectively. After dimethylation of 1,3‐diol 14 (Me 3 OBF 4 , Proton sponge ® , CH 2 Cl 2 , RT), cleavage of the PMB group of the alcohol at C31 was performed with DDQ at this stage to avoid potential interference with the conjugated triene later on and the corresponding alcohol was converted into a TES ether to afford the C16–C46 subunit 15 (64 %, three steps from 14 ). The stage was set for the assembly of the entire carbon framework by the key Suzuki–Miyaura coupling with alkenyl iodide 17 , which in turn had been prepared previously from ( S )‐Roche ester .…”
Section: Figurementioning
confidence: 99%
“…>95:5; d.r.=diastereomeric ratio), according to the well documented 1,5‐ anti (C31–C27) and 1,3‐ syn (C27–C29) stereocontrol in the aldol and reduction processes, respectively. After dimethylation of 1,3‐diol 14 (Me 3 OBF 4 , Proton sponge ® , CH 2 Cl 2 , RT), cleavage of the PMB group of the alcohol at C31 was performed with DDQ at this stage to avoid potential interference with the conjugated triene later on and the corresponding alcohol was converted into a TES ether to afford the C16–C46 subunit 15 (64 %, three steps from 14 ). The stage was set for the assembly of the entire carbon framework by the key Suzuki–Miyaura coupling with alkenyl iodide 17 , which in turn had been prepared previously from ( S )‐Roche ester .…”
Section: Figurementioning
confidence: 99%
“…An aldol coupling with 139 was envisaged to install the pendant side chain, while the macrocyclic core would be constructed from a substrate-controlled aldol reaction between C14-C29 ketone 137 and C1-C13 aldehyde 138, which was posited to give the Felkin-Anh product. [70] These three fragments would then be assembled through the four highlighted aldol disconnections. Initial synthetic studies for the C1-C13 fragment found that any extended manipulations involving lower C1 oxidation states resulted in unavoidable alkene isomerisation.…”
Section: Dictyostatinmentioning
confidence: 99%
“…They display high levels of stereocontrol in boron-mediated anti-aldol reactions 5e,25 and have been widely used in propionate total syntheses. 26 The origin of the high levels of p-face selectivity in these reactions can be traced to the relative steric and electronic contributions of the substituents (H, Me, OBz) of the derived E-enolate 43. For such (E)-enol borinates, there is a strong preference for the proton to reside in an ecliptic conformation with regard to the double bond in order to minimize 1,3-allylic strain.…”
Section: Scheme 9 Paterson Anti-aldol Reactionmentioning
confidence: 99%